2015
DOI: 10.5120/ijca2015907610
|View full text |Cite
|
Sign up to set email alerts
|

The use of ICT among Teachers of Science and Non-science Subjects in Private and Public Secondary Schools in Tanzania: A case of Dodoma Municipality

Abstract: In Tanzania, there have been conceited efforts to integrate various technologies, particularly, Information and Communication Technology (ICT) in the education system.The key stakeholders for these efforts are teachers who are working at the very base of the Tanzanian education systems which include primary schools and secondary schools. The private sector has embarked the same initiatives to utilize ICT in teaching and learning processes. In this paper, a comparison in the extent of the utilization of ICT amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…These gender distinctions can also influence educators' attitudes, abilities, and the use of information and communication technology (ICT) (Lawrence & Tar, 2018;Lindqvist & Pettersson, 2019). For instance, male teachers are reported to utilize ICT more frequently than their female counterparts (Daramola, 2022;Gilbert et al, 2015). However, attitudes toward computers can vary, with women often exhibiting less favorable views (Scherer et al, 2021;Tondeur et al, 2016).…”
Section: The Concepts Of Gendermentioning
confidence: 99%
“…These gender distinctions can also influence educators' attitudes, abilities, and the use of information and communication technology (ICT) (Lawrence & Tar, 2018;Lindqvist & Pettersson, 2019). For instance, male teachers are reported to utilize ICT more frequently than their female counterparts (Daramola, 2022;Gilbert et al, 2015). However, attitudes toward computers can vary, with women often exhibiting less favorable views (Scherer et al, 2021;Tondeur et al, 2016).…”
Section: The Concepts Of Gendermentioning
confidence: 99%
“…In Slovenia, a study conducted by Štemberger and Čotar Konrad [34] discovered that the low level of professional competence of teachers affects teachers' pedagogical attitudes to using digital lesson content for teaching. The study by Gilbert, Ismail and Manyilizu [10] found a shortage of training as one factor affecting teachers' attitudes toward using digital lesson content for teaching and learning. The study conducted in Tanzania by Ndibalema [20] reported a lack of teachers' training from educational colleges regarding digital lesson contents as a significant factor affecting teachers' attitudes in using digital lesson contents for teaching and learning.…”
Section: An Overview On Using Digital Lesson Contents In Teaching And...mentioning
confidence: 99%
“…For example, Ndibalema [20] found that teachers need to gain a better pedagogical competence towards using ICT for teaching and learning due to a lack of readiness, poor training and poor professional support from school management. Likewise, Gilbert et al [11] found that secondary school teachers had low teaching techniques caused by a lack of training in using digital lessons for the teaching and learning process. This shows that the teachers' digital competence is a challenge that needs more consideration for supporting teachers in the teaching and learning process to attain the expected learning needs and quality education.…”
Section: An Overview On Using Digital Lesson Contents For Teaching An...mentioning
confidence: 99%